The approach to automatic generation of test plan for complex systems - Бєляков, О. О.; Севастьян, А. С. (Problems of Informatization and Control, 2016)
Test planning phase is important for the test and minimizing resources used in tests. Planning ofcomplex systems requires consideration of a large number of parameters. Using traditionalapproaches to solving the problem of planning is not appropriate for certain complex systems. Thearticle analyzed the existing methods of forming a plan for testing of complex systems and theproposed approach for formation flight test plans